2015
DOI: 10.7150/thno.11758
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Controlled Intracellular Self-Assembly of 18F Nanoparticles for Enhanced MicroPET Imaging of Tumor

Abstract: Herein, we report the development of a new “smart” radioactive probe (i.e., 1) which can undergo furin-controlled condensation and self-assembly of radioactive nanoparticles (i.e., 1-NPs) in tumor cells and its application for enhanced microPET imaging of tumors in nude mice co-injected with its cold analog (i.e., 1-Cold). Furin-controlled condensation of 1-Cold and self-assembly of its nanoparticles (i.e., 1-Cold-NPs) in vitro were validated and characterized with HPLC, mass spectra, SEM, and TEM analyses. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…We used the fluorescence imaging of cancer cells to compare the intracellular fluorescence quenching effects among the probes of 1 , 1‐Fmoc , and Cypate. To minimize the interference from intracellular Cys with the CBT‐Cys condensation of 1 or 1‐Fmoc , we used 50 × 10 −6 m Biotin‐Cystamine‐Cys(Fmoc)‐Lys‐CBT ( G , Section S2.1 in the Supporting Information) to coincubate with 1 or 1‐Fmoc throughout the cell experiments . Alamar Blue assay indicated that, even at a high concentration of 400 × 10 −6 m , G did not induce cytotoxicity towards biotin receptor‐overexpressing HeLa cells which were incubated with G for 1 h, washed, and incubated for another 24 h (Figure S15a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We used the fluorescence imaging of cancer cells to compare the intracellular fluorescence quenching effects among the probes of 1 , 1‐Fmoc , and Cypate. To minimize the interference from intracellular Cys with the CBT‐Cys condensation of 1 or 1‐Fmoc , we used 50 × 10 −6 m Biotin‐Cystamine‐Cys(Fmoc)‐Lys‐CBT ( G , Section S2.1 in the Supporting Information) to coincubate with 1 or 1‐Fmoc throughout the cell experiments . Alamar Blue assay indicated that, even at a high concentration of 400 × 10 −6 m , G did not induce cytotoxicity towards biotin receptor‐overexpressing HeLa cells which were incubated with G for 1 h, washed, and incubated for another 24 h (Figure S15a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with that of a positive control probe, PET image of the drug‐treated tumor in mouse injected with [ 18 F]C‐SNAT showed obviously enhanced contrast in in vivo. Inspired by this work, Liang and co‐workers reported a “smart” radioactive probe Acetyl‐Arg‐Val‐Arg‐Arg‐Cys(StBu)‐Lys( 18 F‐FB)‐CBT (i.e., 9 in Figure 7 a) that, once co‐injected with its cold analog (i.e., 9‐Cold ), underwent furin‐controlled condensation and self‐assembly of radioactive nanoparticles for enhanced micro‐PET imaging of tumors in nude mice . The underlying reason for this co‐injection strategy lies in the very low chemical concentration (7.1 pmol kg −1 for PET imaging in this work) of the radioactive probe 9 for PET imaging.…”
Section: Intracellular Self‐assembly Of Nanoprobes For Rimentioning
confidence: 99%
“…Tumors are indicated by white arrows. Reproduced with permission . Copyright 2015, Ivyspring International Publisher.…”
Section: Intracellular Self‐assembly Of Nanoprobes For Rimentioning
confidence: 99%
“…Recently, magnetic resonance imaging (Chen et al., ; Yuan et al., ), positron emission tomography (Liu et al., ), and fluorescence imaging (Li et al., ) techniques have been developed to directly detect the tumor‐related protease in some studies. In particular, fluorescent probes have attracted much attention due to their advantages of real‐time imaging and high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%